Quels paysages dans les images produites autour de l’itinéraire touristique Estrada Real (Minas Gerais, Brésil) ? - Philippe Beringuier; Allaoua Saadi (Confins)
Well beyond preconceived and rather controversial ideas, Brazil’s landscapes show, To Whom It May Concern, a diversified journey amidst the nature and culture in a continental country. However, except for the case of visual consumption of noble places, landscape valuation within the touristic activity is still at an embryonic stage. As a tourist route that runs through the states of São Paulo, Rio de Janeiro and Minas Gerais over approximately 1200 km, Estrada Real aims at imposing itself as the end product of rural and cultural tourism of Brazil. Started in 1999 with strong support from advertising and marketing, this route implements a scenic highlight of the territories it crosses by several means, the most important media being a luxurious iconography (beautiful books, glossy paper magazines, post cards). In this context, we focus on how the question of landscape was addressed to in this iconography. We analyzed therefore the production of an imagery based on a corpus limited to postcards and magazines published by the Estrada Real Institute, seeking to identify and distinguish in that material the nature of the landscape displayed, and the values and qualities attributed to them. It is strange to find both landscape homogeneity expressed by the different images produced, and almost absence of rural landscapes which is the basic unit of these territories. This selective imagery provides sometimes a simplistic and conformist vision, especially articulated around the built heritage, therefore corresponding to the expectations of various target groups addressed by this touristic product. Thus, this vision imposes a landscape perspective mixed with a look of nostalgia, a heritage pride, and an aesthetic where the scenario serves as the stage of playful and sports activities, and to the well-being of a wealthy and up-to-dated public. Finally, we argue that the landscapes that could serve as support for an innovative tourism, differentiated from the general touristic supply, are actually restricted to conservative and classic records. As an exchange value, the landscape vision implemented by the Estrada Real Institute shows incomplete landscape imagery, and gradually imposes its standard reading and valuation codes.